Combining Active Learning Strategies: Performances and Experiences of Grade School Filipino Students - Pacala, Frank Angelo A. (International Journal of Social Learning (IJSL), 2021)
This study combined computer simulation and predict-observe-explain as a new strategy known as Computer Simulation Supported Predict-Observe-Explain (CSSPOE) to explore other ways to facilitate the teaching and learning in physics. This strategy was tested in determining the conceptual understanding and scientific reasoning among grade school Filipino students. A quasi-experimental method was used to gather quantitative data from 38 participants then a case study was used to acquire information from the students. After the CSSPOE intervention, post-test results showed that students had positive conceptual changes, and this increase was significant. The interview data showed that participants pointed out the affordances of CSSPOE, such as visualization, autonomy, recognition of alternative conceptions, and consequently accommodating the scientific notions, and noticing the departure of the strategy from the usual lecture method. The recommendation is to adapt CSSPOE in the K to 12 science curriculum or even in college Physics classes. Physics teachers should strive to utilize constructivist and active learning approaches like CSSPOE.